Oxidative Esterification of 5‐Hydroxymethylfurfural under Flow Conditions Using a Bimetallic Co/Ru Catalyst. Issue 13 (12th May 2020) - Salazar, Abel; Linke, Alexander; Eckelt, Reinhard; Quade, Antje; Kragl, Udo; Mejía, Esteban
Abstract: Furanic di‐carboxylate derivatives of 5‐Hydroxymethylfurfural (HMF) are nowadays important in the polymer industry as they are used as building blocks for bio‐based polyesters. The high reactivity of HMF compels to avoid harsh synthetic conditions. Therefore, developing mild catalytic processes for its selective oxidation is a challenging task. Herein, we report the first oxidative esterification of HMF to dimethyl furan‐2, 5‐dicarboxylate (FDCM) under flow conditions using oxygen as oxidant. For that purpose, a new series of nitrogen‐doped carbon‐supported bimetallic Co/Ru heterogeneous catalysts were prepared and characterized by XRD, XPS and N2 physisorption. These analyses revealed that the porosity of the materials and order of impregnation of the metals to the carbon supports lead to varying catalytic activities. Under optimized conditions the flow reactor showed a 15‐fold increase on the production of FDCM compared to batch conditions. Abstract : Flow chemistry : The first oxidative esterification of HMF under flow regime was achieved with excellent conversion (98 %) and good selectivity towards FDCM (57 %) using a heterogeneous bimetallic catalyst mixture based on Cox Oy and RuOx nanoparticles supported on mesoporous carbon. Overall, under flow regime, a >15‐fold increase on the production of FDCM was obtained in comparison to batch conditions.